Sistemas FiWi 5G NR baseados em Fronthauls de fibra ??ptica e FSO - Lopes, Celso Henrique de Souza (2020)
This Dissertation reports the implementations of Fiber-Wireless (FiWi) systems for the fifth-generation of cellular networks (5G), utilizing the 5G New Radio (NR) standard and fronthauls based on analog radio over fiber (A-RoF) and free-space optical (FSO). The proposed technological solutions imply in three main contributions over the State-of-othe-Art. The first one refers to the investigation and application of the A-RoF technique in FiWi systems for simultaneously transmitting LTE-A and 5G NR signals, coexisting in the 700 MHz band, using a dual drive Mach-Zehnder modulator (DD-MZM). Its cabled fronthaul is composed by 12.5 km of single-mode fiber for transporting the 4G and 5G signals, before being radiated through a 10-m femtocell, attaining 182 Mbps throughput. The second contribution is a regarding a FiWi system, which operates in two different 5G scenarios. Initially, the following RF signals are transported a 25-km optical link: F-OFDM (Filtered Orthogonal Frequency Division Multiplexing) signal at 700 MHz, aiming to serve wireless rural area networks (WRAN); five LTE-A sub-bands, exploiting the contiguous intraband aggregation mode at 2.24 GHz; a 5G NR signal at 2.35 GHz for eMBB (enhanced Mobile Broadband) applications. The proposed system provide 1 Gbps throughput, after propagation in either of optical and electrical domains. Finally, the third step is concerning the implementation of a hybrid system using RoF and FSO for network fronthaul, beyond a wireless access network. This proposal is devoted to outdoor WRAN at 700 MHz and indoor and outdoor eMBB applications at 3.5 GHz and 26 GHz, respectively. In this architecture, F-OFDM, M-QAM (MultiLevel Quadrature Amplitude Modulation) and 5G NR signals are applied in order to reach 3 Gbps throughput using RoF/FSO and 1.4 Gbps using RoF/ FSO/Wireless.